Leadership Strategies for Motivating Students: Insights from English Language Learning in Indonesian Senior High Schools - Asrifan, Andi; Dewi, Anita Candra (Development: Studies in Educational Management and Leadership, 2023)
One of the major things that university students have to go through is the learning activity. Achieving one's goals is believed to have a strong correlation with motivation. English proficiency is influenced by pupils' intrinsic willingness to study the language. The purpose of this research was to determine if there is a correlation between the level of interest that second graders at SMA Negeri 2 Sidrap have in studying English and their actual academic performance. The results demonstrated a strong relationship between students' motivation to study English and their actual progress in doing so. The results of the students' English proficiency exam and their motivational surveys corroborated this. Initially, the computed r-value, which was determined using the SPSS 21 Program, was greater than the table value at the 5% and 1% significant levels, or 0.367 < 0.852 > 0.47. Furthermore, when looking at the correlation between student motivation and English language proficiency, it was found that, for the sample class, 72.59% of the variance in student achievement was attributable to student motivation (variable X), while 25.41% was impacted by other factors.